Analysis of Mustahik Empowerment Program in Indonesia: The Case of Non-State Zakat Organization - Mawardi Mawardi; Budi Trianto; Masrizal Masrizal (Universitas Muhammadiyah Yogyakarta, 2022)
The mustahik (the poor and the needy) empowerment program is one of the priority activities carried out by the zakat institution. This study aims to determine whether organizational support and entrepreneurial characteristics possessed by mustahik affect the success of the mustahik empowerment program. This study also aims to determine whether the mustahik empowerment program can alleviate poverty. This research was conducted utilizing Partial Least Square-Structural Equation Modelling (PLS-SEM) method. The population in this study was the mustahiks who received empowerment programs from non-governmental zakat organizations in Pekanbaru City, with a total sample of 60 mustahiks. The results of this study found that there was a positive and significant relationship between organizational support and the mustahik empowerment program. This study also uncovered a significant positive relationship between entrepreneurial characteristics and the mustahik empowerment program. It was also unveiled that the mustahik empowerment program had a positive and significant relationship with the success of poverty alleviation. These results imply that organizational support and entrepreneurial characteristics are important variables in the mustahik empowerment program. Therefore, zakat institutions must pay more attention to these variables to get maximum results in poverty alleviation.